Silicon: quantum dot photovoltage triodes - Wen Zhou (Nature Portfolio, 2021)
While Silicon is widely used for electronic devices, its band-gap limits its use for infrared detection. Here, Zheng et al present a method for overcoming this limitation, by integrating colloidal quantum dots, with the resulting structure exhibiting high sensitivity to infrared radiation.